Use of the national quality registry to monitor health-related quality of life of children with type 1 diabetes: A pilot study. (March 2015) - Petersson, Christina; Huus, Karina; Samuelsson, Ulf; Hanberger, Lena; Akesson, Karin
The management of diabetes is complicated, as treatment affects the everyday life of both children and their families. To enable optimal care for children with type 1 diabetes, it is important to highlight health-related quality of life (HrQoL) as well as medical outcomes to detect psychological problems that otherwise could be missed. The aim was to study HrQoL in children and adolescents with type 1 diabetes dependent on gender, age and co-morbidity and to study the consistency between children's self-reporting and parents' proxy reporting. The cross-sectional data were collected using the questionnaire DISABKIDS Chronic Generic Measure and the DISABKIDS diabetes module. Parents in the proxy report perceived their children's HrQoL to be lower than children themselves. Boys reported their HrQoL to be better than girls. Results show that living with an additional disease has an impact on the HrQoL, which is an important factor to consider in the quality registry. Assessing HrQoL on a routine basis may facilitate detection and discussion of HrQoL-related questions in the national quality registry.